Vivências da pessoa com câncer frente a iminência da morte - Prado, Eleandro do (2016)
Thinking about death can be frightening and painful, but it can be a time to focus and share the expectations and concerns. The choice to deepen ourselves on the needs of patients who experience terminality as the focus of our professional attention is justified by the fragility and lack usually imposed as a result of approaching death. In this way, this care to cancer patients approaching death has essential character, in order to alleviate suffering and promote quality of life. But not before understanding their needs, revealing their feelings and desires and, above all, consider their choices. Thus, this study aimed to understand the daily life of cancer patients who experience the process of death and dying. For this, this qualitative research was guided by existential phenomenology of Martin Heidegger, who enabled to understand this moment of terminality. The protagonists of this study were 11 cancer patients with advanced disease, treated in a non-governmental institution of reference assistance to the patient in a vulnerable situation, in a municipality of Northwest of Paraná, in the period from November 2015 to March 2016. In order to meet the objectives of this study, we used the taped interview to ask these people the following guiding questions: ?How has been your experience at this stage of the disease?? and ?How have you been living with the impossibility of healing your disease?? to capture their speeches. For data analysis, we followed the steps outlined by Paula, and to maintain the anonymity of patients, we named them with character names of the book: ?The Little Prince?. The results of the analyses revealed the experiences of cancer patients in advanced stage, as well as their feelings and needs at this process, expressed through the ontological themes: Meeting with the inevitable possibility of death; Finding themselves by suffering; Transcending the existential anguish through spirituality, Facing the death and dying process, Unveiling the suffering from the perspective of the patient in the imminence of death and Staying alone before death. The interpretation of the subjects showed that the diagnosis of cancer aroused feelings of pain, despair and surprise at the finitude reality that the disease imposes, and such evidence led us to believe that almost as bad as being diagnosed with cancer is realizing with cancer, also due to the stigma of suffering and death that this disease still carries. It is also realized that by becoming the disease incurable, death is imposed as an ever closer horizon, bringing feelings of disappointment and fragility. This shock involving the patient facing the possibility of death demonstrated that, although death is a natural phenomenon, it is not seen as such in our culture, but as a fearsome episode by being-in-the-world during its staying-in-the-world. When they perceive themselves immersed in this finitude of life condition in their daily lives, the patients reflect on their desires and perceptions, seeking a new way of living, showing their true existence. We concluded that, by understanding the needs and experiences of the being-sick at the death, it is feasible that impersonal and inauthentic attitudes can transcend to a new level of assistance, and besides leading health professionals to reflect about the relationship with these beings, generate subsidies for the development of strategies to work with the patients in terminal illness and their families, welcoming these in their doubts, hesitations, and beyond their physical needs, to enter in their biopsychosocial world